Differential coexpression of FoxP1, FoxP2, and FoxP4 in the Zebra Finch (Taeniopygia guttata) song system. Issue 9 (2nd April 2015) - Mendoza, Ezequiel; Tokarev, Kirill; Düring, Daniel N.; Retamosa, Eva Camarillo; Weiss, Michael; Arpenik, Nshdejan; Scharff, Constance
Abstract Heterozygous disruptions of the Forkhead transcription factor FoxP2 impair acquisition of speech and language. Experimental downregulation in brain region Area X of the avian ortholog FoxP2 disrupts song learning in juvenile male zebra finches. In vitro, transcriptional activity of FoxP2 requires dimerization with itself or with paralogs FoxP1 and FoxP4. Whether this is the case in vivo is unknown. To provide the means for future functional studies we cloned FoxP4 from zebra finches and compared regional and cellular coexpression of FoxP1, FoxP2, and FoxP4 mRNA and protein in brains of juvenile and adult male zebra finches. In the telencephalic song nuclei HVC, RA, and Area X, the three investigated FoxPs were either expressed alone or occurred in specific combinations with each other, as shown by double in situ hybridization and triple immunohistochemistry. FoxP1 and FoxP4 but not FoxP2 were expressed in RA and in the HVCRA and HVCX projection neurons. In Area X and the surrounding striatum the density of neurons expressing all three FoxPs together or FoxP1 and FoxP4 together was significantly higher than the density of neurons expressing other combinations. Interestingly, the proportions of Area X neurons expressing particular combinations of FoxPs remained constant at all ages. In addition, FoxP‐expressing neurons in adult Area X express dopamine receptors 1A, 1B, and 2. Together, these data provide the first evidence that Area X neurons can coexpress all avian FoxP subfamily members, thus allowing for a variety of regulatory possibilities via heterodimerization that could impact song behavior in zebra finches. J. Comp. Neurol. 523:1318–1340, 2015. © 2014 Wiley Periodicals, Inc.